FIRM CHARACTERISTICS AND EARNINGS MANAGEMENT IN LISTED SINGAPOREAN CORPORATIONS - Efva Octavina Donata Gozali; Ruth Samantha Hamzah; Chomsah Novianti Pratiwi; Marissa Octari (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2021)
The study aims to examine the association of firms characteristics comprise of firm age, firm size, leverage, and profitability to earnings management (EM). The data is collected from listed Singaporean corporation in Singapore stock exchange (SGX) in the period of 2017 and 2018. Purposive sampling and panel data regression were employed as the sampling and analysis method, respectively. Our results are based on a large sample of 852 firm-year observations. The results show that firm age and firm size significantly affected EM, meanwhile, leverage and profitability indicate insignificant effects to EM. In addition, these results provide information to investors and potential investors regarding future investment decisions.